Persistence and switching patterns of oral migraine prophylactic medications among patients with chronic migraine: A retrospective claims analysis. (April 2017) - Hepp, Zsolt; Dodick, David W; Varon, Sepideh F; Chia, Jenny; Matthew, Nitya; Gillard, Patrick; Hansen, Ryan N; Devine, Emily Beth
Background: Migraine prevention guidelines recommend oral prophylactic medications for patients with frequent headache. This study examined oral migraine preventive medication (OMPM) treatment patterns by evaluating medication persistence, switching, and re-initiation in patients with chronic migraine (CM). Methods: A retrospective US claims analysis (Truven Health MarketScan® Databases) evaluated patients ≥18 years old diagnosed with CM who had initiated an OMPM between 1 January, 2008 and 30 September, 2012. Treatment persistence was measured at six and 12 months' follow-up. Time-to-discontinuation was assessed for each OMPM and compared using Cox regression models. Among those who discontinued, the proportion that switched OMPMs within 60 days or re-initiated treatment between 61 to 365 days, and their associated persistence rates, were also assessed. Results: A total of 8707 patients met the inclusion/exclusion criteria. Persistence to the initial OMPM was 25% at six months and 14% at 12 months. Based on Kaplan-Meier curves, a sharp decline of patients discontinuing was observed by 30 days, and approximately half discontinued by 60 days. Similar trends in time-to-discontinuation were seen following the second or third OMPM. Amitriptyline, gabapentin, and nortriptyline had significantly higher likelihood of non-persistence compared with topiramate. Among patients who discontinued, 23% switched to another prophylactic and 41% re-initiated therapy within one year. Among patients who switched, persistence was between 10 to 13% and among re-initiated patients, persistence was between 4 to 8% at 12 months. Conclusions: Persistence to OMPMs is poor at six months and declines further by 12 months. Switching between OMPMs is common, but results indicate that persistence worsens as patients cycle through various OMPMs.